Chronic expanding hematoma in the liver: a case report - Atsuki Taniguchi; Takeyoshi Nishiyama; Jun Kozai; Izuru Endo; Nobuyuki Watanabe (Surgical Case Reports)
Abstract Background A hematoma that gradually increases over a chronic course of months or longer is defined as a chronic expanding hematoma (CEH). CEHs often develop in the limbs and on body surfaces that are susceptible to external stimuli. CEHs in the intrathoracic or intraperitoneal organs are uncommon, with liver CEHs being particularly rare worldwide. Case presentation A 57-year-old woman was previously diagnosed with a giant cyst in the right liver lobe, with a longer axis of approximately 15 cm. Abdominal ultrasonography findings suggested a complex cyst, and she was referred to our hospital for further inspection. Although CEH was suspected, it was difficult to exclude malignant diseases such as intraductal papillary neoplasm of the bile duct and cystadenocarcinoma. There was a possibility of malignant disease and the exclusion of surrounding organs due to tumor growth. Therefore, a right hepatectomy was performed. Pathological examination revealed a pseudocyst containing a clot, which was consistent with CEH. Conclusions CEH rarely occurs in the liver; however, it is necessary to consider CEH when a slow-growing hepatic mass that shows a mosaic pattern on magnetic resonance imaging is found.